ИНТЕРНЕТ ТАРМАҒЫНА ҚОСЫЛЫЎДЫҢ ЕҢ ӘПИЎАЙЫ УСЫЛЫ - Аламинов, М.Х.; Утемуратов, Т.Р. (FAN va JAMIYAT, 2018)
The article deals with one of the easiest ways of connection to the Internet. The connection to the Internet with the help of an ADSL modem is one of the easiest ways and it was described and explained in detail.